SIFAT-SIFAT FUNGSI PHI EULER DAN BATAS PRAPETA FUNGSI PHI EULER - Rizkun As Syirazi; Thresye Thresye; Nurul Huda (Mathematics Study Program, Faculty of Mathematics and Natural Sciences, Lambung Mangkurat, 2017)
Little Fermat's theory successfully generalized by Euler using Euler's phi function, The phi function Euler φφ (????????) is defined as the number of not more than ???????? and prime with ????????. Gupta (1981) says not all of the original numbers are a range element φφ. The purpose of this study is to determine the properties of the Euler phi function and determine the lower bound and upper limit of the preample of a number under the phi Euler function. This study is a literature study by collecting and studying various references related to the research topic. The result obtained is the relationship of the original number to the map of the number when it is imposed with the phi Euler function and the Euler's function preleta limits, both the lower and upper limits. The limit can be used to specify the set ofprapeta a number under the phi euler function